Rocking the boat : migration and race in contemporary Spanish music - Bermúdez, Silvia (Toronto Iberic, 2018)
Silvia Bermúdez's fascinating study reveals how Spanish popular music, produced between 1980 and 2013, was the first cultural site to engage in critical debate about ethnicity and race in relation to the immigration patterns that have been changing the social landscape of Spanish society since the late 1970s.